Electrodeposition of flower-like nickel oxide on CVD-grown graphene to develop an electrochemical non-enzymatic biosensor1. Issue 30 (14th August 2015) - Rengaraj, Arunkumar; Haldorai, Yuvaraj; Kwak, Cheol Hwan; Ahn, Seungbae; Jeon, Ki-Joon; Park, Seok Hoon; Han, Young-Kyu; Huh, Yun Suk
<x xml:space="preserve">Abstract</x> An enzyme-free electrochemical cholesterol sensor based on a flower-like NiO/high-quality graphene nanocomposite.